On the Banks of Plum Creek - Wilder, Laura Ingalls; Illustrated by Garth Williams (New York Harper Collins Publishers, 1981)
At first, the Ingalls lived in a sod house in Minnesota. Then Pa built a clean new house beside Plum Creek, buying the materials for it on credit, intending to pay for them with the fall wheat harvest. But just before the harvest, a strange glittering cloud suddenly blocked out the sun. Plunk! Something dropped on Laura's head, and fell to the ground. It was the biggest grasshopper she had ever seen. Millions of them descended over the country-side - and there there was no wheat crop.
Keywords: Frontier and pioneer life -- Families -- Minnesota